The Ulnar Collateral Ligament Responds to Stress in Professional Pitchers. Issue 7 (29th July 2019) - Chalmers, Peter Nissen; English, Joy; Cushman, Dan; Yoon, Steve H.; Schulz, Brian M.; Li, Bernard
Objectives: The ulnar collateral ligament (UCL) is one of the most common sites of injury in baseball pitchers, with 25% of Major League Baseball (MLB) pitchers having undergone surgical reconstruction (UCLR). It remains unknown whether the ligament can respond to the stress of pitching. The purpose this study is to determine the response of the UCL in professional pitchers to pitching through a prospective ultrasonographic study. Methods: This was a prospective study supported by the Major League Baseball Research Committee. All pitchers within a single professional baseball club were enrolled. Pitching exposure history data including number of years pitching and peak pitch velocity were collected. A full ultrasound (US) examination of the ligament was then performed by a single fellowship-trained ultrasonographer with extensive experience with UCL US. This US examination was performed at the beginning of the season and then repeated at end of the season. This US examination included measurement of UCL thickness and valgus laxity, as measured via ulnotrochlear joint opening at 30° of flexion to valgus stress of 10% of the mean pitching torque of 64 Nm. Two US images were saved for each measurement such that all measurements were made twice and analysis was performed on the average. Thirty ultrasounds were measured by a second experienced ultrasonographer to determine inter-rater reliability via intra-class correlation coefficients (ICC). Correlation analyses were performed between pre-season data and pitching exposure data. Both paired and unpaired analyses compared pre- and post-season data. Results: 94 pitchers were included prior to the season and 83 were included at the completion of the season. With player movement in and out of the active roster, follow-up rate was 70% (46/66) of those available. These pitchers were 24±3 years old (mean±standard deviation), had 12±6 years pitching experience, and had peak velocity of 95±2 miles per hour. 13 pitchers (9%) had undergone UCLR prior to enrollment and 9 (6%) underwent UCLR after enrollment. With examination of US data, ICCs were 0.742 for UCL thickness and 0.878 and 0.871 for UCL laxity without and with stress at 30° respectively. Peak pitch velocity positively correlated with UCL thickness (ρ= 0.268, p=0.009) and valgus laxity at 30° (ρ= 0.266, p=0.010). In both paired and unpaired analyses, UCL thickness increased during the season (p=0.006 and 0.033 respectively). In the paired analysis valgus laxity at 30° increased non-significantly (p=0.069) and in the unpaired analysis, valgus laxity at 30° increased significantly (p=0.013). Conclusion: The ulnar collateral ligament responds to stress in professional pitchers. The UCL thickens and becomes more lax in response to higher pitch velocity and more years of pitching. The UCL thickens and valgus laxity increases with the stress of a single season of pitching. Our study will gather data on the same pitchers at the beginning of the next season to understand the healing response of the ligament to rest.